Leakage current mechanism and effect of oxygen vacancy on the leakage current of Bi5Nb3O15 films - Cho, Kyung-Hoon; Choi, Chang-Hak; Choi, Joo-Young; Seong, Tae-Geun; Nahm, Sahn; Kang, Chong-Yun; Yoon, Seok-Jin; Kim, Jong-Hee (ELSEVIER SCI LTD, 2010)
The effect of oxygen partial pressure (OPP) on the leakage current density of Bi5Nb3O15 (B5N3) films grown on Pt electrodes was investigated. The leakage current density was very high for the film grown under a low OPP of 1.7 mTorr, but was significantly reduced by the subsequent annealing under a high oxygen pressure or for the film grown under high OPP of 5.1 mTorr. The variation of the leakage current density with OPP was explained by the number of oxygen vacancies, which produced electron trap sites at the interface between the Pt electrode and the B5N3 film-Schottky emission was postulated as the leakage current mechanism of the B5N3 films. The barrier height between the Pt electrode and the B5N3 film grown under a high OPP of 5.1 mTorr was approximately 1.55 eV, but decreased to 0.81 eV for the film grown under a low OPP of 1.7 mTorr due to the presence of the oxygen vacancy. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: ELECTRICAL-PROPERTIES; THIN-FILMS; DIELECTRIC-PROPERTIES; MIM CAPACITORS; BI3NBO7